YOSHLARDA EKOLOGIK XAVFSIZLIK MADANIYATINI SHAKLLANTIRISHGA DOIR MASALALARDA INNOVATSION YONDASHUV - Muxtorova, L.A. (SCIENCE and SOCIETY, 2020)
The article focuses on the systematic organization of environmental education, the promotion of environmental education and safety culture among youth, the further improvement of the ecology with the involvement of advanced innovative technologies, the love and care of schoolchildren issues of enhancing knowledge and skills aimed at preserving the pupil.